Stabilization of the carrier-envelope offset frequency of an Yb:KYW femtosecond laser for the generation of an XUV comb for He+ spectroscopy - Gonzalez, Jorge Moreno (2021)
In this work, the carrier-envelope offset (CEO) frequency of an Yb:KYW frequency comb was detected and stabilized. The stabilization of the Yb:KYW frequency comb is an important step in a larger scale experiment to perform spectroscopy on the yet unexplored 1S-2S two-photon transition in He+, by means of the generation of an XUV frequency comb. The output from the Yb:KYW mode-locked laser consists of 100 fs pulses emitted at a 40 MHz repetition rate and spectrally centered at 1033 nm, which were amplified, compressed and spectrally broadened up to an octave of frequencies. This allowed measuring the CEO frequency through f-2f interferometry, and its stabilization via feedback to the Yb:KYW laser’s pump current. By simultaneously controlling the CEO frequency and the frequency one optical mode of the comb (with an independent setup), all degrees of freedom in the frequency comb are locked, and the system is fully stabilized. We report on the design and construction of a fiber amplifier, pulse compressor, f-2f interferometer and phase-locked loop system for the aforementioned goals, and present proof of their successful operation on the stabilization of the frequency comb.